Optimization of the stress discontinuity value at the interface of a cylindrical stainless steel substrate and electroless Ni-P coating. (27th September 2019) - Baranwal, Rishav Kumar; Hassan, Tarik; Agarwal, Gopal; Sarkar, Subhasish; Majumdar, Gautam
Abstract: Electroless coating and electrolytic coating can be easily differentiated by the use of electricity in the respective processes. The former does not require any electricity for its operation. The advantages include uniform deposition of coating material on the substrate. Besides, nonconductive materials can also be coated by this process. The most important and challenging work in the coating industry nowadays is to apply the electroless plating process on different type of material at a wide range of static and dynamic loading conditions. This literature mainly focuses on the stress distribution along a radial path at the coating and substrate interface of a cylindrical pressure vessel coated with the basic Ni-P coating at static loading condition. There is a total of nine models prepared in Ansys and the Von Mises stress distribution is obtained consecutively. For obtaining the stress distribution, a separate path is created radially and the stress values are plotted for each model separately. In each case, the cylinder thickness is kept constant (2 mm) but the coating thickness and the internal pressure are varied. In each case, it is observed that there is a sharp discontinuity in stress value at the coating and substrate interface but at the same time, the discontinuity is very much dependent on the internal pressure and coating thickness. Optimization has been done on the response of this stress discontinuity with the applied pressure and the coating thickness as the input parameters. The coating thickness of 45 μ m and pressure 50 kPa shows the least stress discontinuity as well as the most optimized result.